Exercise-induced salivary hormone responses to high-intensity, self-paced running - Leal, D. V.; Taylor, L.; Hough, J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Physical overexertion can lead to detrimental overreaching states without sufficient recovery, which may be identifiable by blunted exercise-induced cortisol and testosterone responses. A running test (RPETP) elicits reproducible plasma cortisol and testosterone elevations (in a healthy state) and may detect blunted hormonal responses in overreached athletes. This current study determined the salivary cortisol and testosterone responses reproducibility to the RPETP, to provide greater practical validity using saliva compared with the previously utilized blood sampling. Second, the relationship between the salivary and plasma responses was assessed.